Chapter 1 Patterns of Death, 1800-2020 Global rates and causes - Davenport, Romola (Taylor & Francis, 2021)
This chapter provides a brief introduction to mortality patterns over the last two centuries, from a global perspective. The period witnessed enormous and ubiquitous rises in life expectancy at birth, from a global average of perhaps 30 years in 1800 to an estimated average of 72.6 years in 2019. Remarkably, these changes took place despite a perhaps seven- to eight-fold increase of the world's population, and in the context of unprecedented increases in the speed and frequency of transmission of infectious diseases as a consequence of urbanization, colonization, technological change, and the globalization of trade. This chapter describes the gradual recession of famine and infectious diseases in now-developed countries before c.1870, the acceleration of improvements in life expectancy 1870-1940. and the much more rapid and global gains since the mid twentieth century, together with a brief account of some of the major reversals to these trends, including the HIV and smoking pandemics. It outlines the broad geography and chronology of changes in patterns of mortality, and introduces debates regarding the roles of economic growth and the roles of medicine and states. It concludes with a brief discussion of recent and future trends.